The Extraction of Natural Liquid Red Colorant Containing Antioxidant from Rosella (Hibiscus sabdarrifa L) Calyx and Its Aplication in Food Products - Isnaini, Lailatul (Jurnal Teknologi Pertanian, 2010)
This experiment was aimed to determine the optimum proportion of rosella calyx : water and extraction temperature on the physicochemical characteristics including antioxidant activity of the pigment extract. Finally, the research was also aimed to determine the possibility to use roselle extract as food colorant in some products. This experiment consisted of two steps. The first step was extracting colorant of rosella calyx using factorial Completely Randomized Design. The first factor was the proportion of rosella calyx and water consisted of three levels (1:3, 1:5, 1:7 (b/v)). The second factor was extraction temperature consisted of three levels (40°C, 50°C, 60°C). The combination of those treatments was conducted in triplicate. The second step was the application of rosella extract in certain type of food products (mangkuk cake, lapis cake, agar pudding, and syrup).    The result showed that the best treatment was obtained from the ratio of rosella calyx:water 1:3 (b/v) and extraction temperature 40°C. The treatment significantly affected 5%) the total acid content, pH, total anthocyanin content, antioxidant activity, yield, color (L+, a*). The best treatment gave physical and chemical characteristic of the extract of rosella calyx as follow total anthocyanin content of 19.092 mg/100 ml, antioxidant activity of 53.68%, total acid of 1.26%, pH of 2.23, yield of 55.88%, lightness of 26.23, and redness of 32.88.  While the best treatment based on sensory evaluation of food product using rosella calyx as a colorant extract was agar pudding.Keywords: rosella calyx, antioxidant, natural liquid colorant, extraction